2012
DOI: 10.1634/theoncologist.2012-0134
|View full text |Cite
|
Sign up to set email alerts
|

Management of Unusual Histological Types of Breast Cancer

Abstract: There is increased understanding of the heterogeneity of breast tumors, with greater emphasis now being placed on histological and molecular profiles and, in particular, their implications for prognosis and therapy. This review addresses breast cancers of unusual histological subtype with an approximate incidence <1%. Given the rarity of these tumors, the literature contains primarily case reports, small series, and population-based studies. Data are heterogeneous and almost entirely retrospective, frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 106 publications
(324 reference statements)
2
43
0
4
Order By: Relevance
“…A previous study demonstrated that triple-negative breast cancer was associated with a higher expression of Ki-67 (21). Future studies are needed to confirm our current finding and to investigate whether targeting RASA1 is a novel therapeutic strategy for controlling triple-negative breast cancer.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A previous study demonstrated that triple-negative breast cancer was associated with a higher expression of Ki-67 (21). Future studies are needed to confirm our current finding and to investigate whether targeting RASA1 is a novel therapeutic strategy for controlling triple-negative breast cancer.…”
Section: Discussionsupporting
confidence: 64%
“…Thus, development of novel strategies for the treatment and prognostic prediction of breast cancer, especially triple-negative breast cancer, may aid in the reduction of breast cancer mortality. For example, identification of genes in breast cancer may be used as novel adjuvant diagnostic and prognostic biomarkers to improve treatment decisions in combination with these parameters (21).…”
Section: Discussionmentioning
confidence: 99%
“…Tracking involves following consumers' movements through detection of an RFID tag in their possession, while profiling is the compilation of a composite picture of consumers from a variety of sources. Public awareness of potential privacy breaches has been raised by well-publicised cases involving companies such as Benetton, Gillette, Prada and Proctor & Gamble (Cadoo & Cadoo, 2004;Cavoukian, 2004;Lockton & Rosenberg, 2005). Such breaches can have significant financial, reputational and legal implications as consumers highlight their concerns through social media sites and government bodies appear more willing to take action.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, encysted papillary breast carcinomas were classified as a variant of ductal carcinoma in situ but recent studies are debating the possibility of an invasive component (13,14). Some studies have demonstrated the lack of myoepithelial cell markers at the periphery and also existence of tumor foci beyond the fibrous capsule of the cysts as evidences of invasion (14,15). Even metastatic disease can occur and the most common site is lymph node (16,17).…”
Section: Discussionmentioning
confidence: 99%